Comportamento de Consumo, COVID-19 e Gestão do Conhecimento: UMA ANÃLISE BIBLIOMÉTRICA - Zimmermann, Cristiane Soethe; Boos de Quadros, Cynthia Morgana; dos Santos, Leomar (Revista de Negócios, 2023)
The post-Covid-19 pandemic scenario, with evident changes in consumer behavior, indicates the need for further studies. Especially for organizations, it is necessary to understand how these transformations can interfere in the way of managing information and impact decision-making through knowledge management of this new reality. This article explores research trends and patterns on consumer behavior in the existing literature from the beginning of the Covid-19 pandemic to July 2022, creating a perspective on the study of consumer behavior, through a bibliometric analysis of articles found in the Scopus database. The result of the bibliometric survey diagnosed that studies on consumer behavior and the Covid-19 pandemic are mainly characterized by themes centered on e-commerce, food consumption, food waste, social distancing and sustainability. The analysis of the articles indicated a growth trend of e-commerce and a greater awareness with regard to food consumption and waste, as well as suggesting an increase in concern about food safety and waste generation. It is expected to contribute to new research related to the highlighted themes.